Rancang Bangun Alat Pemadat Tanah yang Ergonomis dengan Penggerak Motor Bensin - Abdul Hamid (Indonesian Society of Applied Science, 2022)
Soil compaction with simple equipment can result in poor solid soil quality because there are still many lumps of rock/gravel that have not been leveled on the compacted soil. In addition, the use of simple equipment can also cause the level of worker fatigue to increase due to the work of the muscles that are so large and work postures that are not ergonomic. So it is necessary to make soil compactor. In the manufacture of this soil compactor, it is necessary to have a theory or method as guide for the preparation in the process of making the tool. Starting from the calculation of engine power and the framework used, methods of using ergonomics data, such as body dimension analysis on anthropometric data. The results obtained from the design are centrifugal force of 14.8 KN, the weight of the compactor when operating is 79.4 kg, the height of the embankment that can be compacted is 4-5 cm, the compaction area achieved is 250 m²/hour, and the vibration frequency is 3 Hz or 18.85 rad/s. From the manufacture of this tool, it can help the process of soil compaction and increase efficiency and productivity of cultivating land or building floors that will be carried out, especially for construction workers in the Pamekasan.